Interpretive standards and quality control limits for susceptibility tests with ampicillin-sulbactam combination disks. - Barry, A L (1984)
In vitro studies were performed to evaluate susceptibility tests with disks containing 10 micrograms of ampicillin plus 10 micrograms of sulbactam. Interpretive zone standards of less than or equal to 11 mm (resistant), 12 to 13 mm (intermediate), and greater than or equal to 14 mm (susceptible) are proposed. A nine-laboratory coordinated study was performed to establish tentative zone size limits for quality control of ampicillin-sulbactam disks. This included data with a new control strain selected to monitor performance of such combination disks.